The Effect of Smartphone Usage Intensity on Early Childhood's Egocentric Behavior and Aggressiveness at Smart Start Preschool Pluit Timur Raya - Sari, Teen Dian Novita (Kirana Publisher (KNPub), 2025)
This study aims to determine the relationship between the intensity of gadget use and egocentric behavior and aggressiveness in early childhood. The data collection method for this study used a census sampling technique, which means that the population can still be reached, namely 70 students. The measuring instrument used was a scale of smartphone use intensity, egocentrism and aggressiveness which were then analyzed using SPSS. The results of this study indicate that smartphone use affects children's egocentric behavior with the results of sig. value = 0.028 <0.05 and on children's aggressive behavior with the results of sig. value = 0.007 <0.05. The higher the intensity of smartphone use in children, the greater their egocentric and aggressive behavior. Conversely, the lower the intensity of smartphone use, the lower the egocentric and aggressive behavior.